Shakespeare's England. - Marshall Cavendish Corporation (New York : M. Cavendish, 1989)
Describes the lives and times of Henry VIII, Elizabeth I, and William Shakespeare.
Includes index.
Bibliography: p. 62.
Keywords: Henry -- VIII, -- King of England, -- 1491-1547 -- Juvenile literature; Elizabeth -- I, -- Queen of England, -- 1533-1603 -- Juvenile literature; Shakespeare, William, -- 1564-1616 -- Homes and haunts -- Juvenile literature; Henry -- VIII, -- King of England, -- 1491-1547.; Elizabeth -- I, -- Queen of England, -- 1533-1603.; Shakespeare, William, -- 1564-1616.; Queens -- Great Britain -- Biography -- Juvenile literature; Dramatists, English -- Early modern, 1500-1700 -- Biography -- Juvenile literature; Kings, queens, rulers, etc; Authors, English; Great Britain -- History -- Tudors, 1485-1603 -- Biography -- Juvenile literature; Great Britain -- History -- Tudors, 1485-1603.